Comparison of endogenous hormone content and balance in Pinus yunnanensis Franch. seedlings after decapitation - Hu, Zhaoliu; Cheng, Sili; He, Bin; Tang, Guangpeng; Chen, Lin; Chen, Shi; Tang, Junrong; Xu, Yulan; Li, Genqian; Cai, Nianhui (Frontiers in Plant Science, 2025)
Pinus yunnanensis is a pioneer tree species and an important timber tree species for afforestation in barren hills in southwest China. It can improve the degradation of P. yunnanensis germplasm resources by decapitation to get high-quality spikes to establish a cutting nursery. The growth and development of sprouting tillers is the result of coordinated regulation of various endogenous hormones, and finally develops into spikes. We aimed to investigate the content changes of endogenous hormones indole-3-acetic acid (IAA), gibberellin3 (GA3), zeatin (ZT), and abscisic acid (ABA) in P. yunnanensis seedlings after decapitation, and to lay a foundation for hormone regulation mechanism in combination with sprouting ability. The plant were one-year-old P. yunnanensis seedlings, the hormone variation characteristics were clarified by decapitation to promote sprouting, and combined with the sprouting ability to analyze the endogenous hormone variations. Decapitation significantly improved GA3, ZT+GA3, IAA+ZT+GA3, and the early sprouting stage (ESS) of IAA and ABA. ZT was no significant change. Decapitation significantly improved the GA3/ABA, (ZT+GA3)/ABA, (IAA+ZT+GA3)/ABA and the ESS of IAA/ABA, and significantly reduced ZT/IAA in the ESS responded decapitation by changing the contents and the balance. The changes in dynamic balance in GA3, GA3/ABA, (ZT+GA3)/ABA, and (IAA+ZT+GA3)/ABA were the most significant. The sprouts number was significantly positively correlated with GA3, ZT+GA3, IAA+ZT+GA3, GA3/ABA, (ZT+GA3)/ABA, (IAA+ZT+GA3)/ABA, and significant positive correlation with ZT/IAA. Sprouts growth was extremely significantly positively correlated with GA3, GA3/ABA, (ZT+GA3)/ABA, and (IAA+ZT+GA3)/ABA. The hormone contents and ratios regulated the occurrence and germination of growth. Dynamic balance of GA3, GA3/ABA, (ZT+GA3)/ABA, and (IAA+ZT+GA3)/ABA played more important roles in the number and growth of sprouts. GA3 played a crucial regulatory role in promoting the sprouting and growth. IAA, ZT, and ABA played an important regulatory role through the interaction between hormones. The mutual balance of hormones promotes the growth and development of sprouting tillers of P.yunnanensis. This experiment explored the response of endogenous hormone content and ratio changes to tiller sprouting by comparing decapitation and non-decapitation, explored the growth and development law of P. yunnanensis tiller sprouting, shortened the seedlings cycle, and provided a scientific basis for the establishment of cutting nursery.